USING BOSARANG IN ENHANCING STUDENTS’ CREATIVITY ON LEARNING DESCRIPTIVE TEXT - Ratna Dwiyaning Raharjanti (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
This paper discusses how a teacher can encourage the students in learning English which is difficult for some of them. The author found a new way to teach descriptive text that was called BOSARANG (kind of puzzle of arranging people’s body). The purpose of this study is to prove that the use of BOSARANG can increase students’ creativity in making descriptive text especially describing people. This paper uses quasi experimental research which uses pre-test and post-test to compare the result. Based on the research, the result shows that BOSARANG has been proven that it totally increases students’ creativity.